Optical Properties of Nanostructured Silica Structures From Marine Organisms - Mcheik, Ali; Cassaignon, Sophie; Livage, Jacques; Gibaud, Alain; Berthier, Serge; Lopez, Pascal J. (Frontiers in Marine Science, 2018)
Light is important for the growth, behavior and development of both phototrophic and autotrophic organisms. A large diversity of organisms used silica-based materials as internal and external structures. Nano-scaled well-organized silica biomaterials are characterized by a low refractive index and an extremely low absorption coefficient in the visible range, which make them interesting for optical studies. Recent studies on silica materials from glass sponges and diatoms, have pointed out very interesting optical properties, such as light waveguiding, diffraction, focusing and photoluminescence. Light guiding and focusing have been shown to be coupled properties found in spicule of glass sponge or shells of diatoms. Moreover, most of these interesting studies have used purified biomaterials and the properties have addressed in non-aquatic environments, first in order to enhance the index contrast in the structure and second to enhance the spectral distribution. Although there is many evidences that silica biomaterials can present interesting optical properties that might be used for industrial purposes, it is important to emphases that the results were obtained from a few numbers of species. Due to the key roles of light for a large number of marine organisms, the development of experiments with living organisms along with field studies are require to better improve our understanding of the physiological and structural roles played by silica structures.